The determinant of Non-Performing Loan (NPL) toward conventional bank in Malaysia / Nor Atiqah Asnawi - Asnawi, Nor Atiqah (Faculty of Business and Management, 2011)
This study reveals the determinants or factor of non-performing loan toward conventional bank in Malaysia. Toward that, the central bank Malaysia also give a guideline the level of nonperforming loan. Furthermore, the data about non-performing loan for three months is taken from source Bank Negara Malaysia from year 2000 until 2010.To analyze the non-performing loan of conventional bank in Malaysia we used all the data from Bank Negara Malaysia to make a finding. From that, I will identify the factor that contribute the non-performing loan toward conventional bank on Malaysia generally. An analysis that I made, is based on data by quarterly from 2000 until 2010. It includes the data about gross domestic product (GDP), interest rate, inflation rate and non-performing loan for three months. This all the data are needed to justify and proof for this research in order for complete my report.